2007
DOI: 10.4049/jimmunol.179.11.7305
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros Enforces the Costimulatory Requirement for IL2 Gene Expression and Is Required for Anergy Induction in CD4+ T Lymphocytes

Abstract: T cell activation results in dynamic remodeling of the chromatin at the IL2 promoter and induction of IL2 gene transcription. These processes are each dependent upon CD28 costimulation, but the molecular basis for this requirement is not clear. The IL2 promoter contains consensus-binding elements for Ikaros, a lymphocyte-specific zinc-finger DNA-binding protein that can regulate gene expression by recruiting chromatin-remodeling complexes. We find that native Ikaros in CD4+ T cells exhibits sequence-specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(135 citation statements)
references
References 78 publications
5
130
0
Order By: Relevance
“…45,46 Therefore, drug-induced disruption of this axis in T cells may explain the poly-lineage effects that we observed. Analysis of serial samples identified rebound in IKZF1 levels in immune cells with ongoing therapy, which may represent a mechanism of acquired resistance to drug-induced immune activation.…”
Section: Discussionmentioning
confidence: 80%
“…45,46 Therefore, drug-induced disruption of this axis in T cells may explain the poly-lineage effects that we observed. Analysis of serial samples identified rebound in IKZF1 levels in immune cells with ongoing therapy, which may represent a mechanism of acquired resistance to drug-induced immune activation.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, epigenetic silencing of the IL-2 locus may contribute to the impaired IL-2 production in anergic T cells (45). In TSC1KO T cells, Egr2/3, Itch, Grail, and Cbl-b expression is down-regulated compared with WT T cells following induction of anergy, suggesting that TSC1 may promote T-cell anergy through up-regulation of these anergy-inducing molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several genes that are upregulated in anergic CD4 + T cells when there is NFAT but not AP-1 transcriptional activation (20)(21)(22)(23)(24)(25)(26)(27). We therefore determined whether Sirt1, as a HDAC, induces and/or maintains CD4 + T cell tolerance by altering the expression of these anergic genes.…”
Section: Sirt1 Suppresses T Cell-dependent Immunity In Micementioning
confidence: 97%